A broken world : letters, diaries and memories of the Great War - Faulks, Sebastian; Wolf, Hope (London : Hutchinson, 2014)
An illuminating non-fiction anthology of writing on the First World War, in which a lieutenant writes of digging through bodies that have the consistency of Camembert cheese; and a nurse tends a man back to health knowing he will be court-martialled and shot as soon as he is fit.
Includes bibliographical references (pages 281-295).
Keywords: World War, 1914-1918 -- Personal narratives